Vitamin D Supplementation Associated with Acute Respiratory Infection in Exclusively Breastfed Infants (P11-071-19). (13th June 2019) - Hong, Miao; Xiong, Ting; Huang, Junmei; Wu, Yuanjue; Lin, Lixia; Zhang, Zhen; Huang, Li; Gao, Duan; Wang, Huanzhuo; Kang, Chun; Gao, Qin; Yang, Xuefeng; et al.
Abstract: Objectives: To investigate the effect of routine oral vitamin D supplementation on acute respiratory infection in exclusively breastfed infants. Methods: A retrospective analysis from a multi-center population-based prospective cohort study (TMCHC) in Wuhan, China. We retrospectively analyzed the data on ARI and ARI-related hospitalization experience and the vitamin D supplementation history among the exclusively breastfed infants by 6 months of age, from the TMCHC study. We set the first ARI by 6 months of age as the outcome endpoint, and assessed the infants vitamin D supplementation from birth to the outcome endpoint with or without supplementation and supplementation frequencies (≤ 2 days/week, 3–4 days/week, 5–6 days/week,  > 6 days/week). Results: Among 983 exclusively breastfed infants, 433 (44%) had an ARI and 55 (6%) experienced ARI-related hospitalization. Infants with vitamin D supplementation experienced a lower cumulative incidence of ARI than those without by 6 months of age ( P  < 0.001). Vitamin D supplementation was significantly associated with a decreased risk of ARI (OR = 0.19, 95%CI: 0.13-0.30) and ARI-related hospitalization (OR = 0.17, 95%CI: 0.09-0.30) after adjustment for all confounding factors. Additionally, this association represented a dose-response relationship (P for trend < 0.001). Conclusions: Vitamin D supplementation was associated with a reduced risk of ARI and ARI-related hospitalization among exclusively breastfed infants by 6 months of age, suggesting that vitamin D supplementation is a promising strategy for acute respiratory infection prevention at early childhood. Funding Sources: This study is supported by National Program on Basic Research Project of China (NO.2013FY114200), the Fundamental Research Funds for the Central Universities (NO. HUST2016YXZD040), and the National Natural Science Foundation of China (NO. 81573149). Supporting Tables, Images and/or Graphs: